Implementasi Pembelajaran Ilmu Pengetahuan Sosial (IPS) dalam Membentuk Karakter Siswa - Iwan Usma Wardani; I Wayan Lasmawan; I Wayan Kertih (Lembaga Pendidikan Islam Ma'aarif NU Kabupaten Magetan, 2023)
This study aims to find out how the implementation of learning Social Sciences (IPS) in shaping student character and knowing the implementation / implementation of student character education at MI Hamzanwadi No 1 Pancor. This research is a descriptive study using a qualitative approach. The subjects of this study were Social Sciences (IPS) Teachers and Grade IV Elementary School Students with data collection techniques including interviews, observation, documentation, and content analysis. Data validity used data triangulation and method triangulation. The results of the study show that the process of implementing or applying Social Sciences (IPS) learning has been carried out properly in accordance with national education goals and then carrying out character education or forming the character of elementary school students in accordance with the cultural characteristics of the local community.